2007
DOI: 10.1038/sj.onc.1210986
|View full text |Cite
|
Sign up to set email alerts
|

Orphan nuclear receptor estrogen-related receptor-β suppresses in vitro and in vivo growth of prostate cancer cells via p21WAF1/CIP1 induction and as a potential therapeutic target in prostate cancer

Abstract: Recent studies indicate that estrogen-related receptors (ERRs) are involved in similar estrogen receptor (ER) regulatory pathways and play roles in energy and lipid metabolism. Here, we analysed the functional role of ERRb in prostate cancer cell growth regulation in an androgen-sensitive and androgen-insensitive prostate cancer cell lines. ERRb was expressed in normal human prostates, but exhibited a reduced expression in prostate cancer lesions. Stable ERRb expression suppressed significantly cell proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 46 publications
4
90
1
1
Order By: Relevance
“…A recent report suggests that ERR␤ expression results in a better prognosis in breast cancer patients with reduced BCA2 and an increased FST level by controlling these genes (61). In addition, ERR␤ exerts a carcinostatic effect through activation of the p21 tumor suppressor gene and cell cycle regulation, which are not linked to anti-estrogenic action (69,70). In fact, our proliferation assay in MRK-nu-1 triplenegative breast cancer cells indicated a growth inhibitory action of ERR␤ independent of estrogen signaling (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report suggests that ERR␤ expression results in a better prognosis in breast cancer patients with reduced BCA2 and an increased FST level by controlling these genes (61). In addition, ERR␤ exerts a carcinostatic effect through activation of the p21 tumor suppressor gene and cell cycle regulation, which are not linked to anti-estrogenic action (69,70). In fact, our proliferation assay in MRK-nu-1 triplenegative breast cancer cells indicated a growth inhibitory action of ERR␤ independent of estrogen signaling (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Targeted disruption of the ERRß gene in mice resulted in severely impaired placental formation, and the embryo died at 10.5 days post-coitum (38). ERRß overexpressed prostate cancer cell lines displayed more active mitochondria at high membrane potentials and showed improved lipid metabolism (39). Recent work has established that ERRs play a role in regulating energy metabolism and mitochondrial biogenesis and function (37,40).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of prostate cancer cell proliferation was due to cell cycle arrest as demonstrated by the induction of cyclin-dependent kinase inhibitor p21 by ERR and p21/p27 by ERR . Moreover, ERR and ERR -mediated growth inhibition could be potentiated by their specific agonist DY131 and reduced by siRNA (Yu, Wang et al 2007;Yu, Wong et al 2008). The expression of ERR and ERR in prostate cancer is in contrast to ERR in breast cancer cells, colorectal tumor, and malignant colon cells (Cavallini, Notarnicola et al 2005).…”
Section: Errs In Other Cancersmentioning
confidence: 99%
“…Since the over expression of ERR in breast cancer was discovered (Ariazi, Clark et al 2002;Suzuki, Miki et al 2004), additional studies have found an association between the abnormal expression of ERRs and a variety of tumors and cancers such as prostate (Cheung, Yu et al 2005;Yu, Wang et al 2007;Yu, Wong et al 2008), ovarian (Sun, Sehouli et al 2005), colon-rectal (Cavallini, Notarnicola et al 2005) and endometrium (Gao, Sun et al 2006). In neoplastic prostatic tissues, ERR and ERR show levels that are either reduced or undetectable as compared to normal prostatic epithelial cells (Cheung, Yu et al 2005).…”
Section: Errs In Other Cancersmentioning
confidence: 99%